Sensitivity of WRF-HAILCAST Model for Hailstone Detection in Central Lombok on 24 February 2019 - Maulana, Muhammad Ikko Safrilda; Kristianto, Aries (Jurnal Fisika dan Aplikasinya, 2024)
Hail is one type of extreme weather produced by Cumulonimbus clouds or convective clouds. Due to deep convection involve to physical processes and cloud dynamics, hail may occur in Indonesia. WRF-HAILCAST was used in this study to detect hailstone. The HAILCAST model is applied to WRF-ARW version 4.0 and above in WRF-HAILCAST. The purpose of this study was to determine the sensitivity of the WRF-HAILCAST model with a modified WSM6 microphysics scheme to detect hailstones that possible to reach the surface. The maximum reflectivity value, vertical reflectivity, maximum hailstone diameter, and cloud microphysics were all approximated properly as a result of this study. The estimation of maximum diameter hailstone was 1.6 cm at the time of hail occurred, and the graupel mixing ratio showed 2.2 g/kg which represented small hail could be detected in  this model. However, WRF-HAILCAST tends to underestimate and has not been able to estimate the time of hail events according to weather radar properly.